Malva sylvestris leaf powder as a feed additive affects the performance, carcass traits, meat quality attributes, serum antioxidants, stress physiology, intestinal bacterial counts, and gut morphology of broiler chicken - Banday, Mohammad T.; Wani, Manzoor A.; Alqhtani, Haifa A.; Bin-Jumah, May; Rudayni, Hassan A.; Allam, Ahmed A.; Algopishi, Uthman Balgith; Adil, Sheikh (Frontiers in Physiology, 2024)
This study investigated the effect of supplementation of Malva sylvestris leaf powder (MSLP) on production performance of broiler chicken. 240 day-old male VenCobb broiler chicks were distributed randomly into 4 treatments, each replicated 4 times, with 15 birds per replicate. The diets formulated were T1 (Control) given basal diet only, T2 (basal diet +1.0 % MSLP), T3 (basal diet +1.5 % MSLP), and T4 (basal diet +2.0 % MSLP). Highest improvement of 3.83% in the average daily gain (ADG) was recorded in T3 group fed 1.5% Malva powder in the diet when compared to control (P = 0.009). Average daily feed intake (ADFI) tended to decrease with increase in the dose of MSLP in diet, with lowest feed intake in T4 group fed 2 % MSLP in the diet. During the overall period (7-42 d), Feed/gain (F/G) ratio reduced significantly (P = 0.048) in T3 and T4 groups in comparison to control. The dressed and breast meat yield was found significantly (P < 0.05) higher in T3 group with no significance (P > 0.05) in thigh yield. pH and water holding capacity (WHC) of breast meat were found nonsignificant (P > 0.05) between control and various other treatments. Thiobarbituric acidreactive substances (TBARS) significantly (P < 0.05) decreased in T3 and T4. There was no negative effect on the colour coordinates of breast meat among different treatments by inclusion of MSLP in the diet. In comparison to control, serum IgM values increased significantly (P < 0.05) in T3 and T4 groups. SOD showed no difference between various treatments, however, MDA decreased significantly (P < 0.05) in dietary treatments. Serum cortisol increased significantly (P < 0.05) in T4 group when compared to other treatments.Inclusion of Malva powder at 2% level in the diet significantly (P < 0.05) decreased the coliform count when compared to the control birds. Supplemented with Malva powder resulted in a significant (P < 0.05) increase in villus height to crypt depth (VH:CD) ratio of broiler birds in T3 and T4 groups. In conclusion, MSLP supplementation at 1.5 % and 2% resulted in improved production performance of broiler chicken.